Processos de obtenç\~ao de tecnologia militar - José Carlos Albano do Amarante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper discusses different ways to obtain military technology, examining: the autonomous development; the cooperative development in international governmental level; the cooperative development in international business; and technology transfer. For that, the article presents the demand for military equipment for current and future combats, visualizing an emphasis in employment of military resources with increasing sophistication and complexity, using technologies based on robotics, in systemization and in automation, in addition to the defense in cybernetic war. This article analyzes the technological retrenchment, related to sensitive technologies, and opens an alternate port, giving access to the development of these technologies, through the creation of mobilizing programs. This work evaluates eight projects to obtain military technology and draws lessons in different sectors of technology: the missiles MSS1.2 and A-Darter, besides the project Astros II, in the missile sector; the Urutu, Guarani and Gaúcho, in the land vehicles of combat sector; the Tupi class, in the submarine sector; and the AMX aircraft, in air sector.
Keywords: H56; O32; O33; 330; technology obtainment; autonomous development; cooperative development; technology transfer; technological retrenchment; mobilizing programs; technological sector